Ensino religioso e os aspectos formativos da pessoa - Maranguape, Francisco Muniz (2013)
The investigation of theorical nature and eminentement bibliographical stamp articulates ideas and concepts pertinent to Religions Teaching to the Whole formation of the people. Begining winth a conceptual base, talko about the caracterization of Religions Teaching ahile epistemological area and the whole part of the child and young people s in relation to the legistation nowadays, supponted by the Federal Constituion and the Diretrizes and Bases Lan. After thio accupies with the configuration of what the integral formation is, anda the same values the education to the citizenship and moral values, the education to the transcendence and articulates ideas about the liberator Education of Paulo Freire. In the last chaptes it, privileges the sense of the Religions Teaching in a approach that gives a good value the Integral Education, from a criticismo of the moral of banker education ande catechitic of the Religions Teaching winth a large opening to a new mode where it gives support to the necessities to prepare the children and teenagers to a good sociability in a plural world with a multiple gendes and religions creeds.